Case Report: Electroacupuncture combined with transcutaneous auricular vagus nerve stimulation for treating antiseizure medication-resistant juvenile myoclonic epilepsy - Matsuura, Yuto; Murakami, Masaaki; Kawakubo, Yuji; Sakai, Tomomi (Frontiers in Psychiatry, 2025)
BackgroundPatients with juvenile myoclonic epilepsy (JME) are frequently resistant to antiseizure medication (ASM) and can have a significantly impaired quality of life (QOL). This case report examines successful treatment of JME using a combination of electroacupuncture and transcutaneous auricular vagus nerve stimulation (taVNS).Case presentationA 19-year-old Japanese male with a 5-year history of ASM-resistant JME presented with frequent myoclonic and generalized tonic-clonic seizures, daily premonitory auras, and psychological distress. Despite treatment with sodium valproate and clonazepam, he continued to experience multiple seizures weekly and was unable to attend school due to anxiety. After declining surgical vagus nerve stimulation, he sought acupuncture treatment. Weekly sessions of electroacupuncture (ST36 and LR3) and taVNS targeting the left auricular concha were initiated. From the second session, electroacupuncture was intensified at GV20, GV24, and GB18 due to initial symptom worsening.ResultsOver the course of eight sessions, seizure frequency decreased from multiple daily episodes to a single seizure in the final 4 weeks. Premonitory auras and mild-to-moderate seizures also declined significantly. SF-36 assessments at baseline, 1 month, and 2 months revealed improvements across all subscales except physical functioning, with scores for bodily pain, vitality, and social functioning exceeding national norms at the final assessment. Component summary scores for physical, mental, and role/social functioning also improved consistently. The patient resumed school attendance, experienced reduced anxiety regarding seizures, and reported enhanced social engagement.ConclusionThis case suggests that combined electroacupuncture and taVNS may be a promising non-pharmacological adjunct in the treatment of ASM-resistant JME, contributing to improved seizure control and multidimensional QOL outcomes.